2019
DOI: 10.21037/acr.2019.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Salty diabetes: a case series of hypernatremia presenting with diabetic ketoacidosis

Abstract: Hyponatremia is an expected electrolyte resultant in diabetic ketoacidosis (DKA) that presents secondary to the dilutional effect of hyperglycemia. However, hypernatremia in DKA is a rare presentation, more common in the pediatric population, that rides poor morbidity and mortality. We describe three cases of patients presenting with DKA and hypernatremia with altered sensorium and share details on pathophysiology and treatment that expand our understanding amongst clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Even with appropriate management, patients continued to be lethargic, and this was likely due to an effect on the sensorium of high osmolarity. 27 The severity of DKA in our patient may have been triggered by the concurrent COVID-19 infection, despite the absence of typical respiratory symptoms. According to the available evidence, adults with diabetes have a less favorable prognosis when infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Even with appropriate management, patients continued to be lethargic, and this was likely due to an effect on the sensorium of high osmolarity. 27 The severity of DKA in our patient may have been triggered by the concurrent COVID-19 infection, despite the absence of typical respiratory symptoms. According to the available evidence, adults with diabetes have a less favorable prognosis when infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 63%
“…Even with appropriate management, patients continued to be lethargic, and this was likely due to an effect on the sensorium of high osmolarity. 27 …”
Section: Discussionmentioning
confidence: 99%
“…As significant volumes of free fluid are lost (most commonly by polyuria), electrolyte loss (through vomiting and diarrhea) may lag behind, leading to a very unusual occurrence of hypernatremia with osmolytic imbalance[ 4 ]. Although such cases of DKA-induced hypernatremia are infrequent, a 2019 paper reviews the cases of two female patients found to be suffering from hypernatremia secondary to DKA after complaints of altered mental status and other symptoms[ 5 ]. Additionally, a 2020 study describes an altered male T1DM patient with a largely unknown medical history suffering from DKA and severe hypernatremia; aggressive treatment of DKA and fluid management yielded a positive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the patient’s altered mentation, paired with his hyperglycemia on presentation, it is possible that this patient was initially hyponatremic but gradually transitioned to hypernatremia after the loss of hypotonic urine. Also, the patient was acidotic, which has been correlated with the level of altered mentation in DKA [ 11 ]. It may be possible that our patient’s altered mentation also contributed to less ingestion of water, underscored by the total water deficit of 17 liters.…”
Section: Discussionmentioning
confidence: 99%